Предмет: Алгебра,
автор: Аноним
119 решите пожалуйста
Приложения:
Ответы
Автор ответа:
0
а) х^2+2х+3х+6=х(х+2)+3(х+2)=(х+3)(х+2)
б)x^2-5х+5-1= (x^2-1)+5(1-х)=(х-1)(х-4
в)x^2+3х-2х-6=х(х+3)-2(х+3)=(х-2)(х+3)
г) x^2-4х+4-1=x^2-1-4х+4=(х-1)(х+1)-4(х-1)=(х-1)(х-3)
б)x^2-5х+5-1= (x^2-1)+5(1-х)=(х-1)(х-4
в)x^2+3х-2х-6=х(х+3)-2(х+3)=(х-2)(х+3)
г) x^2-4х+4-1=x^2-1-4х+4=(х-1)(х+1)-4(х-1)=(х-1)(х-3)
Похожие вопросы
Предмет: Английский язык,
автор: alinausacova96
Предмет: Другие предметы,
автор: kuserovazuldys84
Предмет: Геометрия,
автор: elobanova889
Предмет: Математика,
автор: okb070882
Предмет: История,
автор: elzaalaya2000